2016
DOI: 10.1108/josm-10-2014-0268
|View full text |Cite
|
Sign up to set email alerts
|

Shopping experiences in visually complex environments: a self-regulation account

Abstract: Purpose Providing satisfying shopping experiences is a major goal in retail management because satisfaction guides re-patronage behavior. This study aims to demonstrate that the visual complexity of an environment’s interior design (i.e., the overall amount of visual information in an environment) influences the shopping experience by impairing customers’ information processing and self-regulation resources. Design/methodology/approach Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 99 publications
(148 reference statements)
0
20
1
1
Order By: Relevance
“…Orth and Wirtz () found that disorganization and complexity in a grocery retail store negatively influences the information processing fluency of the environment, which in turn affects pleasure, attractiveness of environment, and response behaviors. Orth et al () further demonstrated that processing load in a grocery retail store with visual complexity and subsequently reduced perceived self‐control are responsible for the lower level of processing fluency of the environment. Also, Chae and Zhu () found that environmental orderliness in a primed setting can affect self‐regulation as a disordered environment enhances information overload and threatens the individual's sense of personal control, which leads to resource depletion and consequently impairs self‐regulation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Orth and Wirtz () found that disorganization and complexity in a grocery retail store negatively influences the information processing fluency of the environment, which in turn affects pleasure, attractiveness of environment, and response behaviors. Orth et al () further demonstrated that processing load in a grocery retail store with visual complexity and subsequently reduced perceived self‐control are responsible for the lower level of processing fluency of the environment. Also, Chae and Zhu () found that environmental orderliness in a primed setting can affect self‐regulation as a disordered environment enhances information overload and threatens the individual's sense of personal control, which leads to resource depletion and consequently impairs self‐regulation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Such environments negatively affect the anticipated benefits derived from the efficient fulfillment of shopping task than it would in a hedonic shopping situation (Garaus & Wagner, ; Orth et al, ). Orth et al () also suggest that the effect of cognitive load derived from visual complexity on shopping experience is significant and negative for individuals with utilitarian shopping orientation. Therefore, the following is proposed:H6 In a highly crowded retail store, the negative effect of retail shopper confusion on (a) revisit intention, (b) in‐store exploration, (c) spending time, (d) store patronage intention, and (e) unplanned expenditure will be stronger when consumers pursue task‐oriented rather than recreational shopping motivations.H7 In a highly messy retail store, the negative effect of retail shopper confusion on (a) revisit intention, (b) in‐store exploration, (c) spending time, (d) store patronage intention, and (e) unplanned expenditure will be stronger when consumers pursue task‐oriented rather than recreational shopping motivations.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptual fluency concept builds on the processing fluency theory (Schwarz 2004), according to which consumers constantly monitor the effort required to process information cues prevalent in an environment. This effort decreases when the sensory stimulation in a servicescape is simple instead of complex and if consumers process a situation repeatedly (Orth, Wirtz, and McKinney 2016). As fluency per se feels positive (Landwehr, Golla, and Reber 2017), repeated exposure to a simple scent stimulus should translate into improved situational service evaluations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Prior research also demonstrates that conflict and complexity are highly relevant properties in predicting consumers' responses to shopping environments (Deng and Poole 2010;Nasar 1987;Orth et al 2016), while variety and novelty do not appear to reflect the confusion potential of store environments. From an index construction viewpoint, Bollen (2011, p. 362) point out: "removal of a causal indicator might change the nature of the latent variable."…”
Section: Empirical Validationmentioning
confidence: 99%